Mali : Achieving Strong and Inclusive Growth with Macroeconomic Stability - Josz, Christian (Departmental Papers; Departmental Paper ;, 2013)
This note studies Mali's performance in poverty reduction by analyzing household data from surveys in 2001, 2006 and 2009-10. Mali's share of poor households has decreased substantially during the past decade. While the reduction in headcount poverty was more pronounced from 2001-06 when all sectors of Mali's economy grew at a similar pace, economic growth was mainly beneficial to the very poor during 2006-10 when agricultural production boomed.